Determining Interconnectedness of Barriers to Interface Management in Large Construction Projects (Construction Economics and Building, 2022)
This study aims to identify the crucial barriers to interface management and understand the interdependencies in Large Infrastructure Construction Projects (LICP). Three-pronged sequential explanatory mixed methods research is adopted comprising a structured survey of experts (n=102) and semi-structured interviews (n=13). Subsequently, interpretive structural modelling (ISM) integrated with fuzzy protocol is used to analyse pairwise interrelationships among these factors. A ‘Multi-layered IM barrier’ model is developed with ‘Process related issues,’ 'Misaligned incentives among project stakeholders' and 'Frequent Change Orders' as the manifested barriers. On the other hand, this study also prioritized the barriers and classified them as driving, linking, and independent. The outcome of this study presents the interdependence of barriers and classification of barriers, focusing on proactive action on driving barriers, which is crucial to the knowledge of interface management. The impact position of LICP with the identified project issues can be compared against ‘Multi-layered IM barriers’ and can help project teams better strategize IM by focusing on essential barriers. In addition, such exercises can improve the coordination among participants in construction projects. Using a structured approach to identifying interdependencies among barriers to IM is a significant original contribution by the study.